Quality of public services in the field of population administration in malang public administrative mall - Supriyanto, Didik (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The government as a provider of public services needed by the community must be responsible and continue to strive to provide the best service for the sake of improving public services. If we are honest, there is hope that people's satisfaction is a measure of the success of public services provided by the government as a public service provider. The purpose of this study is to determine the Quality of Public Services in the Field of Population Administration in Malang City Public Administration Mall. This research is a descriptive study using a qualitative approach to determine the quality of public services in the field of population administration at the City Administration Mall in Malang. The data analysis technique used is an interactive model. The results showed that the quality of public services in the field of population administration at the Malang City Public Administration Mall was seen from the aspects of physical facilities, reliability, responsiveness, assurance, empathy, namely the Public Services section at the Malang City Public Administration Mall did not meet adequate service facilities to provide services to public. The community is satisfied with the service provided by the Malang City Public Administration Mall in the reliability aspect regarding reliability in handling any public complaints. Employees in terms of helping people who need services, especially people who are confused about services, have been seen between officers and visitors who communicate with each other. Security at the Malang City Public Administration Mall has shown efforts to improve the quality of its services related to providing a sense of security for the community. The empathy given by the Public Administration Mall is by giving a pleasant impression.